Circulating adiponectin and leptin in relation to myelodysplastic syndrome: a case-control study. - Dalamaga, Maria; Nikolaidou, Athina; Karmaniolas, Konstantinos; Hsi, Alex; Chamberland, John; Dionyssiou-Asteriou, Amalia; Mantzoros, Christos S (Oncology, 2007)
OBJECTIVE: Adiponectin plays a protective role in several malignancies, including myeloblastic leukemia, whereas leptin may increase the proliferation of progenitor cells and may stimulate leukemic cell growth in vitro. We investigated the role of adiponectin and leptin levels in the etiopathogenesis of myelodysplastic syndromes (MDS), a preleukemic condition with increasing incidence which has recently been associated with obesity. METHODS: In a case-control study, 101 cases with incident, histologically confirmed primary MDS and 101 controls matched on gender and age were studied between 2004 and 2007, and blood samples were collected. RESULTS: Higher serum adiponectin levels were associated with lower risk of MDS by bivariate analysis and after adjusting for age, gender, body mass index and serum levels of leptin (p < 0.001). Subjects in the third quartile for leptin levels had a lower risk of MDS than controls, and low leptin concentrations were observed in low-risk MDS patients with normal or good prognostic karyotype after adjusting for age, gender and body mass index. CONCLUSIONS: Circulating adiponectin and leptin may play an important role in MDS etiopathogenesis. Future studies are needed to confirm these associations and to explore underlying mechanisms.
Keywords: Adiponectin; Aged; Biomarkers; Biomarkers, Tumor; Case-Control Studies; Female; Humans; Leptin; leukemia; Male; Middle Aged; Myelodysplastic Syndromes; Obesity; Precancerous Conditions; Predictive Value of Tests; Prognosis